PENGARUH DISIPLIN, MOTIVASI DAN KOMITMEN ORGANISASI TERHADAP KINERJA PEGAWAI DI KANTOR PENGADILAN TINGGI MEDAN - Friska Nurmaida; Marudut Sianturi; Rasmulia Sembiring (JURNAL PROINTEGRITA, 2021)
This study aims at determining the effect of discipline, motivation and organizational commitment on employee performance at the Medan High Court. This research is a correlational statistical study, in which the data obtained is disclosed based on data in the field. The time used in research is scheduled in January 2020 - June 2020. The independent variables in this study consist of: discipline (X1), motivation (X2), and organizational commitment (X3), while the dependent variable is performance (Y). The sampling technique in this study uses the saturated sample method. So that the number of samples in this study were 40 respondents. Data analysis was performed using multiple linear regression analysis. The results show that discipline partially had a significant effect on employee performance at the Medan High Court Office with a t-test value of 2.735 > from a t-table of 1.685 or with a significance value of 0.010 < 0.05. Motivation partially has a significant effect on performance at the Medan High Court Office with a t-count value of 3.709> from t-table 1.685 or with a significance value of 0.001 < 0.05. Organizational commitment partially has a significant effect on performance at the Medan High Court Office with a t-value of 2.643 > from t-table 1.685 or with a significance value of 0.025 < 0.05. Discipline, motivation and organizational commitment simultaneously have a significant effect on organizational commitment at the Medan High Court Office with an F-count value of 34,967 > F-table 2.87 or with a significance value of 0,000 < 0.05.